Improving the Bench Testing Method of Sliding Contacts of Electric Transport - Ustymenko, D. V; Diab, Al Said Ahmad Mohammad Ahmad (Science and Transport Progress, 2021)
Purpose. The work is aimed to present the results of a comprehensive study of the bench testing procedure of high-current sliding contact of electric transport, which together provide a basis for proposals, recommendations for improving the standard method of these tests. Methodology. The research is based on two classical methods of scientific research. The first one is the observation and processing of the results of a real experiment in the laboratory; the second is the development of mathematical model for determining the temperature effect in the area of sliding contact on the wear of the contact wire, with subsequent determination of the resource of this sliding contact. Findings. The result of these studies is a list of recommendations on the procedure and content of the program-methodology of bench tests of inserts of current collectors of electric transports. The obtained scientifically substantiated results will allow to assert that their introduction will reduce time, energy and other expenses for performing obligatory bench tests of new samples of current collector inserts. Originality. By means of non-destructive temperature control at the point of current collection of high-current sliding contact, taking into account the temperature limit value during current collection process, for the first time the values of the heating time constant of the «insert fragment – contact wire ring» were obtained for different insert materials. This makes it possible to predict the final result of bench tests as successful or unsuccessful already at the initial testing stage (the first 10 thousand disk passes). Based on statistical processing of experimental data, the dependences of the contact wire wear on the number of test bench passes were obtained, which creates conditions for forecasting the value of contact wire wear during bench tests relative to the reference sample. Practical value. It is experimentally proved that the dependence of the contact wire wear on the number of passes of the test bench disk is linear, which allows accelerated resource testing of high-current sliding contact elements while maintaining the adequacy of the results. In general, the comprehensive application of the received recommendations creates conditions for saving time, energy and other costs when conducting bench tests of sliding contacts of electric transport.